Development of handout teaching materials with a contextual approach to improve students' mathematical understanding - Ifat Sarifayani; Arif Abdul Haqq (International Journal of Education and Humanities, 2022)
This study aims to determine which handout teaching materials with a contextual approach are suitable for use in learning mathematics, and to find out that handout teaching materials with a contextual approach are able to improve students' mathematical understanding. The type of research used is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collected in the form of observation sheets, interviews, questionnaires, and tests of students' mathematical understanding. The handout validation was validated by experts, namely material, language, and media experts, covering aspects of content, presentation, language, and graphics. In the validation results, material experts get a score of 3.44 which states "very valid", the linguist gets a score of 3.69 which states "very valid", and media experts get a score of 3.21 which states "valid". so that the overall average score gets a value of 3.45 which states "very valid". While the student and teacher responses get an average score of 3.25 which states "very practical", and on the effectiveness of the handout teaching materials obtained from the final test results students get a percentage of 71.8% which states "effective". Then on the results of the students' understanding test, they got an n-gain value of 0.6 which stated "medium", that the understanding obtained by students did not decrease or increase so it was relatively moderate